Searching for New Forms of Legitimacy Through Corporate Responsibility Rhetoric - Castelló, Itziar; Lozano, Josep M. 1954- (2011)
This article looks into the process of searching for new forms of legitimacy among firms through corporate discourse. Through the analysis of annual sustainability reports, we have determined the existence of three types of rhetoric: (1) strategic (embedded in the scientific-economic paradigm); (2) institutional (based on the fundamental constructs of Corporate Social Responsibility theories); and (3) dialectic (which aims at improving the discursive quality between the corporations and their stakeholders). Each one of these refers to a different form of legitimacy and is based on distinct theories of the firm analyzed in this article. We claim that dialectic rhetoric seems to signal a new understanding of the firm’s role in society and a search for moral legitimation. However, this new form of rhetoric is still fairly uncommon although its use is growing. Combining theory and business examples, this article may help managers and researchers in the conceptualization of how firms make sense of their role in society and what forms of differentiation they strive for through their rhetoric strategies.
Keywords: Rhetoric; organizational legitimacy; Globalization; Discourse Analysis; Corporate Social Responsibility; Business Ethics; Business and society